Theory of Motivated Cue-Integration and COVID-19: Between Interoception, Somatization, and Radicalization - Shalev, Idit (Frontiers in Psychiatry, 2021)
The global dissemination of COVID-19 creates confusion and ambiguity in nearly every aspect of life, including fear of contagion, heightened awareness of the mortality of self and family members, lack of power, and distrust of experts and decision-makers. In this stressful situation, the question arises as to what mechanisms distinguish between adaptive and maladaptive self-regulation. The theory of Motivated Cue-Integration (MCI) is a novel theory of self-regulation that provides a new perspective on the effect of COVID-19 on self-regulation deficiency as an example of psychological distress. Inspired by predictive coding, social cognition, embodied cognition, and experiential approach, MCI suggests that self-regulation is based on interaction between (1) high-level values and goals, (2) low-level interoceptive and exteroceptive signals, and (3) trust in epistemic authority or a significant other. Motivated Cue-Integration posits that individuals create meaning by making moment-to-moment predictions that affect their interpretation of the experience of ambiguity influenced by their relationship with epistemic authority. According to MCI, deficiency in self-regulation during COVID-19 could result either from over-sensitivity or under-sensitivity to low-level interoceptive and exteroceptive cues; rigidity or ambiguity of high-level goals, poor integration between the two levels of processing as well as distrust in epistemic authority. According to MCI, variations of these deficiencies may occur in various clinical phenomena such as alexithymia and somatization, as well as in social phenomena such as goal radicalization. Based on this reasoning, MCI claims that the mentalization of the relationship between interoceptive cues, exteroceptive cues, goals, and psychological needs of the person, as well as the improvement of confidence in epistemic authority, can promote adaptive self-regulation. Psychological intervention can foster trust in epistemic authority, increase the mentalization of interoceptive and exteroceptive cues, and their association with adaptive goals. As such, the integration of these elements in a way that facilitates incentives pathways and insight fosters a more integrated subjective experience, higher clarity of emotion, and positive internal dialogue which promotes action tendency.